Ministry of the Interior Decree No. 1888 of the Year 2023 Amending Certain Provisions of Ministerial Decree No. 180 of the Year 1964 Concerning the Implementation of Certain Provisions of Law No. 89 of the Year 1960 In Respect Of Admittance And Residence Of Foreigners In The Territories Of The Arab Republic of Egypt And Exit Therefrom = وزارة الداخلية قرار رقم 1888 لسنة 2023 بتعديل بعض أحكام القرار الوزارى رقم 180 لسنة 1964 بشأن تنفيذ بعض أحكام القانون رقم 89 لسنة 1960 فى شأن دخول وإقامة الأجانب بأراضى جمهورية مصر العربية والخروج منها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic